Estudos desenvolvidos pela Empresa Goiana de Pesquisa Agropecuária com Cratylia argentea - Sobrinho, José Marcelino; Nunes, Marcos Rogério (International Center for Tropical Agriculture, 1996)
In 1975, the Empresa Goiana de Pesquisa Agropecuária (EMGOPA) re-initiated its activities of germplasm introduction in Goiás, Brazil. Leucaena leucocephala, Cratylia argentea, Desmodium spp., and Chamaecrista sp. were outstanding among the 1,000 or more legume accessions evaluated. Cratylia argentea is a native plant, characterized by good performance and high dry matter production. Studies on optimum cutting time indicated that April was the best month because later cuttings increased plant damage during frosts. Cratylia argentea is especially tolerant to drought and maintains its foliage for a long time before the next rains. Lime applications in the region's Oxisols enhanced the DM production and nodulation of this species